KONSUMSI DALAM PERSPEKTIF PEMIKIRAN EKONOMI ISLAM MONZER KAHF - Izzah, Siti Nailul (2021)
Monzer Kahf is one of the foremost economists in Islam and sees economics as part of religion. His first book "The Islamic Economy: Analytical Study of Functioning of The Islamic Economic System" was published in 1978 and contains a book on the mathematical analysis of Islamic economics. Monzer Kahf has tried to criticize other economists who emphasize the differences between Muslim and Western economies. The main assumption of Monzer Kahf's famous thought is that he does not have to be a Muslim if he is to accept the Muslim paradigm. Another key assumption is that the state plays a role in planning and controlling. The state and Muslims must work together to achieve the goal of implementing an Islamic economic system. In terms of consumption, there are differences in the Islamic concept of success, and Monzer Kahfi believes that a person's product and consumption behavior conforms to the rules of Allah's non-governmental organization. Therefore, in this article, we explain the theory we use in Monzer Kahf's terms. Monzer Kahfi relates his consumption theory to consumption behavior, consumption balance, Islamic product concepts, and Islamic consumption ethics. From an application point of view, success is balancing consumption by balancing not only the material dimension but also last-day (future) beliefs. They do not harm others and do not divide their wealth into charity, philanthropy and other charities.